Fluid Flow and Cell Proliferation of Mesenchymal Adipose‐Derived Stem Cells in Small‐Scale, Stirred, Single‐Use Bioreactors. Issue 1 (19th December 2012) - Kaiser, Stephan; Jossen, Valentin; Schirmaier, Carmen; Eibl, Dieter; Brill, Silke; van den Bos, Christian; Eibl, Regine; Eibl, Regine; Eibl, Dieter
Abstract The fluid flow and suspension characteristics inside small‐scale, stirred, single‐use bioreactors were investigated experimentally and by means of computational fluid dynamics. The required impeller speeds for homogenous suspension were determined for two microcarrier types. The shear stress level and turbulence distribution were predicted using a numerical model, which was verified by particle image velocimetry measurements. In subsequent cultivations of primary mesencymal adipose‐derived stem cells, up to 31.4‐fold expansion in cell number was achieved for serum concentrations as low as 5 %.